EVALUASI MANAJEMEN PENCEGAHAN STUNTING DI DESA PAYA TAMPAK KECAMATAN PANGKALAN SUSU KABUPATEN LANGKAT - Samrin Samrin; Ismaidar Ismaidar (CERED Indonesia Institute, 2023)
The purpose of this study was to analyze and evaluate stunting management in Paya Tampak Village. The visible problem is that the phenomenon of stunting is still a separate problem in the village, so it needs serious handling. Stunting is defined as growth failure in children under the age of 5 years caused by chronic malnutrition so that children have low height for their age. This research approach is descriptive qualitative by making direct observations in Paya Tampak village. The data analysis technique uses a grounded theory design, which is to analyze research problems using qualitative techniques. The results of this study indicate that stunting has a negative impact on children in later life, such as disrupting brain development, cognitive development, growth faltering, and low immune system. Evaluation of stunting management needs to be done to improve nutritional and cognitive status is needed to reduce the negative impact of stunting on children. The village government to the regional and central governments need to identify stunting management that allows for an increase in the nutritional and cognitive status of children so that stunting problems no longer occur